Cellular and molecular mechanisms of cigarette smoke-induced lung damage and prevention by vitamin C - Roy Siddhartha; Panda Koustubh; Koley Hemanta; Ghosh Arunava; Chattopadhyay Ranajoy; Banerjee Shuvojit; Chattopadhyay Dhrubajyoti; Chatterjee Indu B (BMC, 2008)
Abstract Background Cigarette smoke-induced cellular and molecular mechanisms of lung injury are not clear. Cigarette smoke is a complex mixture containing long-lived radicals, including p-benzosemiquinone that causes oxidative damage. Earlier we had reported that oxidative protein damage is an initial event in smoke-induced lung injury. Considering that p-benzosemiquinone may be a causative factor of lung injury, we have isolated p-benzosemiquinone and compared its pathophysiological effects with cigarette smoke. Since vitamin C is a strong antioxidant, we have also determined the modulatory effect of vitamin C for preventing the pathophysiological events. Methods Vitamin C-restricted guinea pigs were exposed to cigarette smoke (5 cigarettes/day; 2 puffs/cigarette) for 21 days with and without supplementation of 15 mg vitamin C/guinea pig/day. Oxidative damage, apoptosis and lung injury were assessed in vitro, ex vivo in A549 cells as well as in vivo in guinea pigs. Inflammation was measured by neutrophilia in BALF. p-Benzosemiquinone was isolated from freshly prepared aqueous extract of cigarette smoke and characterized by various physico-chemical methods, including mass, NMR and ESR spectroscopy. p-Benzosemiquinone-induced lung damage was examined by intratracheal instillation in guinea pigs. Lung damage was measured by increased air spaces, as evidenced by histology and morphometric analysis. Oxidative protein damage, MMPs, VEGF and VEGFR2 were measured by western blot analysis, and formation of Michael adducts using MALDI-TOF-MS. Apoptosis was evidenced by TUNEL assay, activation of caspase 3, degradation of PARP and increased Bax/Bcl-2 ratio using immunoblot analysis and confocal microscopy. Results Exposure of guinea pigs to cigarette smoke resulted in progressive protein damage, inflammation, apoptosis and lung injury up to 21 days of the experimental period. Administration of 15 mg of vitamin C/guinea pig/day prevented all these pathophysiological effects. p-Benzosemiquinone mimicked cigarette smoke in causing protein modification and apoptosis in vitro and in A549 cells ex vivo as well as apoptosis and lung damage in vivo. All these pathophysiological events were also prevented by vitamin C. Conclusion p-Benzosemiquinone appears to be a major causative factor of cigarette smoke-induced oxidative protein damage that leads to apoptosis and lung injury. The pathophysiological events are prevented by a moderately large dose of vitamin C.